the population in Iraq up to 2035 an analytical study - الاطرقجي, أ.م.د.عبدالغفور محمد سليم; فليح, م.د.مهيب كامل (Journal of Planner and Development, 2012)
The population studies are one of the difficult tasks facing the world in all periods. most of the researchers and who have relationship to population policies and development plans, may have succumbed to the idea that the population problem is based and confined mainly in the rate of increase in population, or the so – called population explosion, and not the content because of its pressure on resources and there is no problem of population if the resources are available and therefore no need for the development and implementation of population policies in any way . While the population policies here should take a range of general and comprehensive in every respect to population and demographic phenomena distribution, not only related to the rate of population increase. This research studies and analyzes the indicators of growth and distribution of population in Iraq to estimate the size of population up to 2035, and suggests the most important population policies required.